Validity of Practicum Guide in Molecular Genetics Course for Bachelor's Student of Biology Study Program of Mathematic and Science Faculty in Universitas Negeri Makassar - Aulya Novira; Oslan Jumadi; Hartono Hartono; Irma Suryani (Biology Teaching and Learning, 2023)
Abstract. The formulation of the problem in this research is how to develop a valid molecular genetics practicum guide with the aim of testing the validity of the practicum guide in molecular genetics courses for undergraduate biology study program students. This type of research is Research and Development (R&D) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The instrument used is a validation sheet filled out by a validator expert. Data was collected through analysis of validation sheets that had been filled in by expert validators and analyzed descriptively in order to obtain data in the form of a validity score. The results showed that practicum guides had an average validity score in the range of 4.5 ≤ Va = 5, in this case it met the very valid criteria.Keywords: ADDIE development model, practicum guide, molecular genetics